IMPLEMENTASI KAJIAN KITAB AL HIKAM KARYA SYEKH IMAM IBNU ATHAILLAH ASSAKANDARI DALAM MEMPERBAIKI BUDI PEKERTI JAMAAH REMAJA BESILAM - Muhammad Rifai; Ahmad Zaki (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
This research was initially motivated by the dynamics of life in adolescents seeking an identity that has good character. in life, of course, we are social, religious and national, so we need knowledge that can control the mind so that we are patient and understanding in dealing with it. The study of the book Al Hikam presented by Sheikh Dr. Zikmal Fuad Ma (Tuan Guru Besilam) provides an understanding that makes the hearts of anyone who listens calm and peaceful. The problems that exist in this world can be overcome because we have studied the wisdom contained in the book Al Hikam. Wisdom or the meaning of life is an important thing for a person. So it is worth making it a life goal. With wisdom, a person can live life sincerely and solely seeking the approval of Allah subhanahu wa ta'ala. Young people who grow and develop in worshiping Allah subhanahu wa ta'ala sometimes have disabilities in their worship. In his worship there are lustful needs such as being cheerful, arrogant and arrogant. So by studying the wisdom contained in the Book of Al Hikam, the aim is to improve the morals of teenagers in accordance with the ideals of the Prophet sallallaahu alaihi wasallam who was sent on this earth to perfect morals. or character, the book Al Hikam is one place to study it.